The relationship between the Five-Factor model and job performance of salespeople in clothing industry in Chengdu - Guo, Yudi (2018)
The research mainly explored the relationship between personality based on the Five-Factor model and job performance of salespeople in clothing industry in Chengdu. During the period, taking use of the online questionnaire, which was divided into three parts including personal information, personality testing and job performance testing, collected information of 390 participates who were from Zara, H&M, Max Mara and Mo&Co respectively. As a consequence, the study proved the personality of salespeople had a certain impact on job performance. Notably, conscientiousness was positively related to the performance, which was same with literature, but extraversion had negative influence, which differed from past researches. The possible reasons might be that the regression model is not correctly specified, and X variables are endogenous. What is more, different requirements for salespeople in different organizations could lead to totally opposite conclusion. In the cheap brands, agreeableness and openness had positive relationship with job performance, but higher scores in neuroticism triggered worse sales performance. However, the results of expensive brands were inverse.